Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(1-\left(\frac{12}{5}+y=\frac{8}{9}\right):\frac{16}{9}=0\)
\(1-\left(\frac{12}{5}+y-\frac{8}{9}\right)=0\times\frac{16}{9}\)
\(1-\left(\frac{12}{5}+y-\frac{8}{9}\right)=0\)
\(\frac{12}{5}+y-\frac{8}{9}=1-0\)
\(\frac{12}{5}-y+\frac{8}{9}=1\)
\(\frac{12}{5}-y=1-\frac{8}{9}\)
\(\frac{12}{5}-y=\frac{1}{9}\)
\(y=\frac{12}{5}-\frac{1}{9}\)
\(y=\frac{108}{45}-\frac{5}{45}\)
\(y=\frac{103}{45}\)
a) $\frac{{14}}{{18}}:\frac{8}{9} = \frac{7}{9}:\frac{8}{9} = \frac{7}{9} \times \frac{9}{8} = \frac{{63}}{{72}} = \frac{7}{8}$
b) $\frac{9}{6}:\frac{3}{{10}} = \frac{3}{2}:\frac{3}{{10}} = \frac{3}{2} \times \frac{{10}}{3} = \frac{{30}}{6} = 5$
c) $\frac{4}{5}:\frac{{10}}{{15}} = \frac{4}{5}:\frac{2}{3} = \frac{4}{5} \times \frac{3}{2} = \frac{{12}}{{10}} = \frac{6}{5}$
d) $\frac{1}{6}:\frac{{21}}{9} = \frac{1}{6}:\frac{7}{3} = \frac{1}{6} \times \frac{3}{7} = \frac{3}{{42}} = \frac{1}{{14}}$
\(\frac{1}{2}:\frac{3}{2}:\frac{5}{4}:\frac{6}{5}:\frac{7}{6}:\frac{8}{7}\)
\(=\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{4}{5}\cdot\frac{5}{6}\cdot\frac{6}{7}\cdot\frac{7}{8}\)
\(=\frac{1\cdot\left(2\cdot5\cdot6\cdot7\right)}{8\cdot3\cdot\left(2\cdot5\cdot6\cdot7\right)}\)
\(=\frac{1}{24}\)
\(\frac{1}{2}\cdot\frac{2}{3}\cdot\frac{3}{4}\cdot\frac{4}{5}\cdot\frac{5}{6}\cdot\frac{6}{7}\cdot\frac{7}{8}\cdot\frac{8}{9}\cdot\frac{9}{10}\)
\(=\frac{1\cdot\left(2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9\right)}{\left(2\cdot3\cdot4\cdot5\cdot6\cdot7\cdot8\cdot9\right)\cdot10}\)
\(=\frac{1}{10}\)
\(3+\frac{2}{5}-\frac{3}{4}\times\frac{4}{5}\)
\(=3+\frac{2}{5}-\frac{3}{4}\)
\(=\frac{3\times20+2\times4-3\times5}{20}\)
\(=\frac{60+8-15}{20}\)
\(=\frac{68-15}{20}\)
\(=\frac{53}{20}\)
\(5-\frac{7}{9}+\frac{2}{3}-\frac{5}{6}:\frac{4}{9}\)
\(=5-\frac{7}{9}+\frac{2}{3}-\frac{45}{24}\)
\(=\frac{5\times72-7\times8+2\times24-45\times3}{72}\)
\(=\frac{360-56+48-135}{72}\)
\(=\frac{217}{72}\)
\(1,\frac{3}{5}+\frac{7}{2}-\frac{4}{7}=\frac{42}{70}+\frac{245}{70}-\frac{40}{70}=\frac{247}{70}\)
\(2,\frac{4}{5}-\frac{1}{3}+\frac{3}{4}=\frac{48}{60}-\frac{20}{60}+\frac{45}{60}=\frac{73}{60}\)
\(3,\frac{1}{3}\times\frac{5}{7}:\frac{7}{2}=\frac{5}{21}:\frac{7}{2}=\frac{10}{147}\)
\(4,\frac{1}{2}:\frac{2}{7}\times\frac{4}{7}=\frac{7}{4}\times\frac{4}{7}=1\)
\(5,\frac{19}{15}\times\frac{3}{7}:\frac{4}{9}=\frac{19}{35}:\frac{4}{9}=\frac{171}{140}\)
\(6,\frac{11}{3}:\frac{9}{16}:\frac{3}{8}=\frac{176}{27}:\frac{3}{8}=\frac{1408}{81}\)
_Chúc bạn học tốt _
a, \(\frac{3}{4}\times\frac{4}{7}+\frac{5}{14}\)
\(=\frac{3}{7}+\frac{5}{14}=\frac{6}{14}+\frac{5}{14}=\frac{11}{14}\)
b, \(\frac{5}{14}+\frac{9}{7}\div\frac{3}{4}\)
\(=\frac{5}{14}+\frac{9}{7}\times\frac{4}{3}=\frac{5}{14}+\frac{12}{7}=\frac{5}{14}+\frac{24}{14}=\frac{29}{14}\)
c, \(\frac{12}{17}\div x=\frac{3}{5}\)
\(x=\frac{12}{17}\div\frac{3}{5}=\frac{12}{17}\times\frac{5}{3}=\frac{20}{17}\)
\(\frac{3}{4}X\frac{4}{7}+\frac{5}{14}\)
\(=\frac{3}{7}+\frac{5}{14}\)
\(=\frac{6}{14}+\frac{5}{14}\)
\(=\frac{11}{14}\)
\(\frac{7}{8}\)x \(\frac{8}{9}\)x \(\frac{9}{10}\)
= \(\frac{7}{9}\)x \(\frac{9}{10}\)
= \(\frac{7}{10}\)
1 x \(\frac{2}{3}\): \(\frac{4}{3}\) : \(\frac{5}{4}\)
= \(\frac{2}{3}\)x \(\frac{3}{4}\)x \(\frac{4}{5}\)
= \(\frac{1}{2}\) x \(\frac{4}{5}\)
= \(\frac{2}{5}\)
\(\frac{7}{8}\times\frac{8}{9}\times\frac{9}{10}\)
\(=\frac{7\times8\times9}{8\times9\times10}\)
\(=\frac{7}{10}\)
\(1\times\frac{2}{3}:\frac{4}{3}:\frac{5}{4}\)
\(=\frac{2}{3}\times\frac{3}{4}\times\frac{4}{5}\)
\(=\frac{2}{5}\)
12/14 + 15/20 + 6/7 + 3/4
= ( 12/14 + 6/7 ) + ( 15/20 + 3/4 )
= ( 6/7 + 6/7 ) + ( 3/4 + 3/4 )
= 12/7 + 6/4
= 48/28 + 42/28
= 90/28
= 45/14
Tham khảo nha !!!
\(\dfrac{3}{7}+\dfrac{5}{9}=\dfrac{27}{63}+\dfrac{35}{63}=\dfrac{62}{63}\)
\(\dfrac{3}{7}+\dfrac{5}{9}\)
\(=\dfrac{27}{63}+\dfrac{35}{63}\)
\(=\dfrac{27+35}{63}\)
\(=\dfrac{62}{63}\)